Pencegahan Stunting di Kalimantan Timur: Strategi Inovatif dan Kebijakan Kolaboratif untuk Meningkatkan Nutrisi dan Kesehatan Anak - Muhammad Nur Madani; Yuliansyah Hufat San; Derry Try Sandy (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2024)
This study aimed to gain new knowledge and discoveries, especially those related to nutrition in East Kalimantan, with stunting rates showing significant disparities between districts/cities. The latest data shows East Kutai recorded the highest stunting rate at 29%, far above the WHO threshold of 20%. The analysis method used was article content analysis. Research articles that met the criteria were then collected, and the findings were summarized. The data came from a survey conducted by the Ministry of Health in 34 provinces in Indonesia and East Kalimantan Province. Paser and West Kutai Districts also showed a high prevalence of stunting, at 22.4% and 22% respectively. This condition indicates that local factors, including access to health services and nutrition education, play a major role in exacerbating this problem, although cities such as Balikpapan and Samarinda have better infrastructure, significant stunting rates (21.6% and 24.4%) indicate that urbanization is not always directly proportional to improvements in children’s nutritional status. This study proposes several innovative strategies to address the problem of stunting, including community-based approaches, tailored nutrition intervention programs, improving access and quality of health services, nutrition education in schools, public awareness campaigns, multi-sectoral policy integration, and research and data development. Implementing these strategies is expected to reduce stunting rates and improve the health and welfare of the community in East Kalimantan.